(Critical Thinking Ability of Class VIII Students in terms of Conceptual Knowledge and Mathematical Dispositions) (Universitas Negeri Semarang, 2022)
The purpose of this study was to describe the critical thinking skills (CT) of grade VIII A Madrasah Stanawiyah (MTs.) Sultan Agung Sukolilo students in terms of conceptual knowledge (CK) and mathematical disposition (MD). This research is qualitative research. The subjects of this study were students of class VIII A MTs. Sultan Agung Sukolilo which is divided into nine categories based on CK and MD. The results of this study are two students in the category of sufficient conceptual knowledge and high mathematical disposition have good CT abilities. Both students can analyze, develop, and create well. Twenty-six students from nine categories had moderate CT abilities. Meanwhile, six students from the categories of good conceptual knowledge and low mathematical disposition, sufficient conceptual knowledge and moderate mathematical disposition, sufficient conceptual knowledge- low mathematical disposition, and poor conceptual knowledge and moderate mathematical disposition were included in the category of students with poor CT abilities. the results above, most students have moderate critical thinking skills, namely 76% of students, it is necessary to improve critical thinking skills both in analyzing, based, and creating. Based on the results of tests, some students think critically in analyzing, namely determining relations, domains, codomains, and ranges, and finding sets and re-coordinating sets that are good. Meanwhile, in making new associations related to everyday life and determining the relations of an image and about stories, it is still lacking.